2(k+1)+2(1-9k)=y

Simple and best practice solution for 2(k+1)+2(1-9k)=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(k+1)+2(1-9k)=y equation:


Simplifying
2(k + 1) + 2(1 + -9k) = y

Reorder the terms:
2(1 + k) + 2(1 + -9k) = y
(1 * 2 + k * 2) + 2(1 + -9k) = y
(2 + 2k) + 2(1 + -9k) = y
2 + 2k + (1 * 2 + -9k * 2) = y
2 + 2k + (2 + -18k) = y

Reorder the terms:
2 + 2 + 2k + -18k = y

Combine like terms: 2 + 2 = 4
4 + 2k + -18k = y

Combine like terms: 2k + -18k = -16k
4 + -16k = y

Solving
4 + -16k = y

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -16k = -4 + y

Combine like terms: 4 + -4 = 0
0 + -16k = -4 + y
-16k = -4 + y

Divide each side by '-16'.
k = 0.25 + -0.0625y

Simplifying
k = 0.25 + -0.0625y

See similar equations:

| 5(10k+9)-7(1-4k)=y | | 74x+7= | | (2x^2+2x+18)+(3x^2-4x+13)-(x^2+15x-2)=0 | | 6(x-3)=-3x-54 | | f(x)=9x^2+54x+71 | | (5g^3+2)-(6g+6)-(4g^3-3g)=0 | | (7b^4-4)-(7b^3-5)+(4b^4-3b^3)=0 | | secx+cosx=0 | | 2r^2-10r-48=0 | | 3(9n+5)+8(10n-9)=y | | 4(3x-1)+9(-5x+2)=y | | 9(6a-10)+2(-6a+8)=y | | 6(4k-5)-4k=y | | -9(2-10a)+8a=y | | 3(1+8m)=y | | 4(9+4x)=y | | f(x)=2x^2-36x+169 | | 6x+43=300 | | -6(8+x)-7=y | | 7(-6m-8)+9m=y | | 10(-2b+8)+2=y | | 10(1-6v)=y | | 10(1-6v)=y | | 7(x*6)+y=119 | | -6(b-2)=y | | 5x^3=8 | | x^4+x^3+x+4=0 | | -7(10p-7)=y | | -4p-2p=y | | 2a-10a=y | | 1-8n-9n=y | | x*7+45=80 |

Equations solver categories